GIS-Based Irrigation Network Mapping for Inundation Mitigation in Plosobuden Village, Lamongan: Pemetaan Jaringan Irigasi Berbasis GIS untuk Mitigasi Genangan di Desa Plosobuden, Lamongan - Sutrisno, Eko; Sarasanty, Diah; Asmorowati, Erna Tri; Bashirah, Ainin; Sholikhah, Faizatus; Wijihapsari, Sunarti (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This service activity was motivated by the problem of inundation in the pond area in Plosobuden Village caused by the limited capacity of the river network and irrigation canals and the lack of spatial databases in its management. Conceptually, this service refers to a spatial-based water resource management approach (GIS-based water resource management) and community-based approach. The purpose of the service is to increase community capacity in identifying and managing inundation through GIS-based mapping of irrigation networks. The methods used include: (1) satellite image acquisition and interpretation, (2) digitization and mapping using QGIS, (3) channel and runoff capacity analysis, and (4) participatory training and mentoring. Evaluation indicators include: (a) increased community understanding measured through pre-test and post-test, and (b) participation level measured from participants' attendance and active involvement during service. The results showed the preparation of irrigation network maps and the identification of inundation critical points. Quantitatively, there was an increase in comprehension scores from the average from 42.7% to 80.3% of the total registered participants. These findings show that GIS integration and participatory approaches are effective in supporting community-based irrigation management